Perang Salib dalam Bingkai Sejarah - Syamzan Syukur (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2011)
Crusade represents the war that happened between Muslims and Cristians in the past. This fight is called Crusade, which is by Cristian people referred as holy war, because the expedition of Christian military hence the Cross sign as unifier attribute and as holy war symbol in attacking to Islamic world. According to writer analysis, the magnifier of Cristian people is understood thouroghly as religious emotion of the Cristian people. With the the Cross sign symbol, they would easily inspired the religious emotion of Cristian people. Provenly, in three period of attacks, some Cristians took a great participation in the the war. In a period of that war, winning and fail was coming exchangeably between the legion of Islam and Cristian people.